Neuropsychological predictors of quality of life in focal epilepsy - Meneses, Rute F. (2009)
Spontaneous complaints of outpatients with focal epilepsy often stress the relationship between cognitive deficits and Quality of Life (QOL). Consequently, the aim of the present study was to find the best neuropsychological predictors of QOL in individuals with focal epilepsy, in order to guide their ambulatory health care. A sample of 71 Portuguese patients was studied: 40 female, 47 married, with a mean age of 37.48 years (S.D. = 11.79, 16–62), mean education of 7.93 (S.D. = 4.05, 3–17), and focal epilepsy of moderate severity. A Socio-demographic and Clinical Questionnaire, the SF-36 v1, the Cognitive Functioning Scale from the ESI-55, a Seizure Control scale (items from the Liverpool Seizure Severity Scale), and several neuropsychological tests were used. Semantic Fluency was the only predictor of Physical Functioning, Role Functioning – Physical, and Mental Health; I.A. Test predicted Bodily Pain; and AttentiveMatrices predicted General Health, Vitality, and Role Functioning – Emotional. The Mental Component of the SF-36 v1 was predicted by Attentive Matrices, and the Physical Component was predicted by Semantic Fluency. Cognitive Functioning was predicted by the Token Test. Social Functioning and Seizure Control presented no statistically significant correlation with the neuropsychological indicators used. These results underscore the importance of cognitive performance to the QOL of individuals with focal epilepsy, supporting the systematic screening of cognitive performance in this population. Additionally, they suggest cognitive rehabilitation has the potential to improve these individuals’ QOL.